Vulnerability of South African women workers in the COVID-19 pandemic - Saloshni, Naidoo; Nithiseelan, Naidoo Rajen (Frontiers in Public Health, 2022)
On March 5th, 2020, the first SARS-CoV-2 (COVID-19) case was diagnosed in South Africa. Shortly after, President Cyril Ramaphosa, declared a National State of Disaster placing the country under “lockdown”. Two years later the National State of Disaster was terminated on 15 March 2022 with more than 3.9 million cases of COVID-19 and more than 100 000 fatalities recorded. In the context of this pandemic the vulnerability of working women in South Africa increased considerably. In South Africa most women workers find themselves in vulnerable employment as domestic help in private households, traders in the informal economy, and small-scale agriculture with no employment contracts or health insurance cover. During the pandemic, women workers had to further deal with the socioeconomic vulnerability of their employment, dual domestic and working responsibilities and those infected with COVID-19, with the clinical sequelae of the disease. The government implemented several policies to assist workers and reduce the risk faced by vulnerable workers, including women. Despite these initiatives, long-term policies aimed at socioeconomic protection and employment creation that focus on women workers are required to address the negative impact of the COVD-19 pandemic as experienced by women workers in South Africa.